Synthesis and characterization of FexCo3−xO4 nanoparticles for sensor applications - Pradeep V.C.S.S.V.; Alla S.K.; Sharma A.; B A.; Vasundhara M.; A.Gangwar; Shaw S.K.; Prasad N.K. (My University, 2025)
In the present investigation, ferromagnetic behavior has been identified for the Fe substituted Co3O4 nanoparticles which produced by microwave refluxing method. The detailed investigation of magnetic properties with different concentration of Fe substitutions revealed the ferromagnetic behavior due to the anti-ferromagnetic interaction of magnetic sublattices. High resolution transmission electron microscopy (HR-TEM) studies confirmed the spherical morphology of nanoparticles with a size between 8 and 20 nm. The absence of other phases than Co3O4 was ruled out by XRD, TEM and Raman spectroscopy analyses. X-ray photoelectron spectroscopy analysis evidenced the presence of Fe3+, Co2+ and Co3+ ions in the samples. Photoemission spectra confirmed the absence of defect states in the samples. Magnetic measurement analysis revealed that the strong influence of Fe concentration on the saturation magnetization values of Co3O4 nanoparticles. These structural and optical properties of the Fe substituted Co3O4 are suitable for various gas sensor applications. © 2022 Elsevier B.V.